Lung disease caused by ABCA3 mutations. Issue 3 (11th August 2016) - Kröner, Carolin; Wittmann, Thomas; Reu, Simone; Teusch, Veronika; Klemme, Mathias; Rauch, Daniela; Hengst, Meike; Kappler, Matthias; Cobanoglu, Nazan; Sismanlar, Tugba; Aslan, Ayse T; Campo, Ilaria; et al.
Abstract : Background: Knowledge about the clinical spectrum of lung disease caused by variations in the ATP binding cassette subfamily A member 3 (ABCA3) gene is limited. Here we describe genotype-phenotype correlations in a European cohort. Methods: We retrospectively analysed baseline and outcome characteristics of 40 patients with two disease-causing ABCA3 mutations collected between 2001 and 2015. Results: Of 22 homozygous (15 male) and 18 compound heterozygous patients (3 male), 37 presented with neonatal respiratory distress syndrome as term babies. At follow-up, two major phenotypes are documented: patients with (1) early lethal mutations subdivided into (1a) dying within the first 6 months or (1b) before the age of 5 years, and (2) patients with prolonged survival into childhood, adolescence or adulthood. Patients with null/null mutations predicting complete ABCA3 deficiency died within the 1st weeks to months of life, while those with null/other or other/other mutations had a more variable presentation and outcome. Treatment with exogenous surfactant, systemic steroids, hydroxychloroquine and whole lung lavages had apparent but many times transient effects in individual subjects. Conclusions: Overall long-term (>5 years) survival of subjects with two disease-causing ABCA3 mutations was <20%. Response to therapies needs to be ascertained in randomised controlled trials.